PACAP-38 and PACAP(6–38) Degranulate Rat Meningeal Mast Cells via the Orphan MrgB3-Receptor - Pedersen, Sara Hougaard; la Cour, Sanne Hage; Calloe, Kirstine; Hauser, Frank; Olesen, Jes; Klaerke, Dan Arne; Jansen-Olesen, Inger (Frontiers in Cellular Neuroscience, 2019)
Infusion of pituitary adenylate cyclase activating peptide-38 (PACAP-38) provokes migraine attacks in migraineurs and headache in non-migraineurs. Adverse events like long-lasting flushing and heat sensation can be terminated with oral antihistamine treatment, indicating the involvement of mast cell activation after PACAP-infusion. Degranulation of rat peritoneal mast cells was provoked by several isoforms of PACAP via previously unknown receptor pharmacology. The effect might thus be mediated either via specific splice variants of the PAC1-receptor or via an unknown receptor for PACAP-38. In the present study, we characterize degranulation of rat meningeal mast cells in response to PACAP-receptor ligands. Furthermore, we investigate if PACAP-38-induced mast cell degranulation is mediated via PAC1-receptor splice variants and/or via the orphan Mas-related G-protein coupled member B3 (MrgB3)-receptor. To address this, the pharmacological effect of different PACAP isoforms on meningeal mast cell degranulation was investigated in the hemisected skull model after toluidine blue staining followed by microscopic quantification. Presence of mRNA encoding PAC1-receptor splice variants and the MrgB3-receptor in rat mast cells was investigated by Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) analysis. The effect of PACAP isoforms on PAC1- and MrgB3-receptor-expressing Xenopus laevis oocytes were performed by two-electrode voltage-clamp (TEVC) electrophysiology. PACAP-38 is a more potent mast cell degranulating agent than Pituitary Adenylate Cyclase Activating Peptide-27 (PACAP-27) in the meninges. Presence of mRNA encoding the PAC1-receptor and its different splice variants could not be detected in peritoneal mast cells by RT-PCR, whereas the orphan MrgB3-receptor, recently suggested to be a mediator of basic secretagogues-induced mast cell degranulation, was widely present. In PAC1-receptor-expressing Xenopus laevis oocytes both PACAP-38, PACAP-27 and the specific PAC1-receptor agonist maxadilan were equipotent, however, only PACAP-38 showed a significant degranulatory effect on mast cells. We confirmed Pituitary Adenylate Cyclase Activating Peptide(6–38) [PACAP(6–38)] to be a PAC1-receptor antagonist, and we demonstrated that it is a potent mast cell degranulator and have an agonistic effect on MrgB3-receptors expressed in oocytes. The present study provides evidence that PACAP-induced mast cell degranulation in rat is mediated through a putative new PACAP-receptor with the order of potency being: PACAP-38 = PACAP(6–38) > > PACAP-27 = maxadilan. The results suggest that the observed responses are mediated via the orphan MrgB3-receptor.